Peningkatan Produksi Asam Glutamat Corynebacterium glutamicum dengan Penambahan Penisilin pada Fase Logaritmik - Mursyanti, Exsyupransia; Lestari, Sri (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2005)
One way to increase production and excretion of glutamic acid was to increase cell's permeability. Penicillin has a potency to change the cell permeability by inhibitng cell wall synthesis. However, penicillin treatment was effective only for actively dividing cells. Therefore, such a research was done to study on the time of penicillin treatment to the medium, so that it can be found optimal cell biomass to produce maximum glutamic acid. The cell utilized in the research was Corynebacterium glutamicum IFO 12168 that was in batch cultured. Concentration of penicillin added was 5 unit/ml and treated at incubation periods 12, 14, 16, 18, and 20 hours, respectively, after inoculation. The steps of the research were as follows purification test, growth pattern, and glutamic acid production. Parameters measured at the end of the fermentation were cell biomass, reduced sugar concentration, medium’s pH, and glutamic acid concentration. Data was analysed utilizing Anova and the significant difference between treatments were tested using Duncan’s Multiple Range Test (DMRT). The growh pattern shown that logarithmic phase was reached at 2 to 22 hrs of incubation periods, therefore the treatment of penicillin was given at 12, 14, 16, 18, and 20 hrs of incubation periods. Cell biomass produced was corelate with the concentration of reduced sugar in the medium. Measured pH of the medium at the end of the fermentation was on the pH range for the growth of C. glutanicum. The research concluded that Penicillin treatment was able to increase significantly the glutamic acid production compatred to control treatment. Time accuracy of penicillin treatment to produce maximum glutamic acid (154319,60 µg/ml) was on 18 hrs of incubation period.